Kajian Pendekatan Literasi Dalam Penanggulangan Geng Antar Pelajar Pada Pembelajaran IPS Di SMK TI Bali Global Denpasar - Tjokorda Istri Agung Rai Sintha Devi (Jurnal Ragam Pengabdian, 2026)
Student gangs are a social issue that can disrupt character development and the effectiveness of learning processes in schools. This study aims to analyze the phenomenon of student gangs, the factors contributing to their formation, their impact on students’ behavior and Social Studies learning, and the implementation of a literacy approach as a strategy to address the issue at SMK TI Bali Global Denpasar. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that student gangs were characterized by the formation of exclusive groups with strong identities and solidarity. The factors contributing to gang formation included identity crises and low self-control, as well as peer influence, family conditions, social media, and insufficient school supervision. The existence of gangs contributed to aggressive behavior, bullying, student conflicts, and decreased effectiveness of Social Studies learning. The implementation of a literacy approach through case analysis, group discussions, critical reflection, and the use of digital media as learning resources was found to enhance students’ critical awareness, empathy, tolerance, and ability to understand and solve social problems constructively. Therefore, the literacy approach can serve as an effective preventive and corrective strategy in addressing student gang phenomena in schools.